2017
DOI: 10.1016/j.jsams.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary nitrate supplementation on the adaptations to sprint interval training in previously untrained males

Abstract: 5Objectives: Dietary nitrate can improve repeated high-intensity and supramaximal exercise 6 performance, although the effect on adaptations to training has received limited attention. The 7 purpose of this study was to investigate the effects of dietary nitrate on the response to 3-weeks 8 of sprint interval training (SIT). Design: Randomized control trial. Methods: Twenty-seven 9 untrained males (Age: 28 ± 7 y, V̇O 2Max : 42 ± 7 ml·kg -1 ·min -1 ) completed an incremental 10 exercise test at the beginning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…Two studies have also recently explored the effects of NO 3 − supplementation on the adaptations to SIT in normoxia [140, 141]. Muggeridge et al [140] reported greater improvements in maximal work rate during incremental exercise and indices of repeated high-intensity performance in participants who ingested NO 3 − versus placebo prior to SIT sessions (3 × 4–6 maximal 15 s cycle ergometry sprints per week, for 3 weeks).…”
Section: Training In Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have also recently explored the effects of NO 3 − supplementation on the adaptations to SIT in normoxia [140, 141]. Muggeridge et al [140] reported greater improvements in maximal work rate during incremental exercise and indices of repeated high-intensity performance in participants who ingested NO 3 − versus placebo prior to SIT sessions (3 × 4–6 maximal 15 s cycle ergometry sprints per week, for 3 weeks).…”
Section: Training In Hypoxiamentioning
confidence: 99%
“…Muggeridge et al [140] reported greater improvements in maximal work rate during incremental exercise and indices of repeated high-intensity performance in participants who ingested NO 3 − versus placebo prior to SIT sessions (3 × 4–6 maximal 15 s cycle ergometry sprints per week, for 3 weeks). Thompson et al [141] also demonstrated greater improvements in peak work rate during incremental exercise in individuals who performed SIT (3–4 × 4–5 maximal 30 s cycle ergometry sprints per week for 4 weeks) with NO 3 − compared with both training individuals given a placebo and NO 3 − -supplemented individuals who did not train.…”
Section: Training In Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, more research needs to be conducted and it should be noted that the majority of works to date (five of the eight studies report no effect or a decrease in performance) do not support the ergogenic effect of dietary inorganic nitrate for repeated bouts of high-intensity exercise. Currently, there are several chronic HIIT studies (3-6 weeks) that have examined the potential for nitrate to augment training adaptations [134,141,[144][145][146][147]. Two studies found an increase in whole-body oxygen uptake (VO 2 max) following HIIT training (three-four times per week; four-five Wingates per session) in recreationally active participants with nitrate supplementation (12.8 mmol NO 3 divided into two servings) compared to HIIT and placebo [141,146], while others found no enhancement of aerobic power [134,144,147,148].…”
Section: Nitratementioning
confidence: 99%
“…Currently, there are several chronic HIIT studies (3-6 weeks) that have examined the potential for nitrate to augment training adaptations [134,141,[144][145][146][147]. Two studies found an increase in whole-body oxygen uptake (VO 2 max) following HIIT training (three-four times per week; four-five Wingates per session) in recreationally active participants with nitrate supplementation (12.8 mmol NO 3 divided into two servings) compared to HIIT and placebo [141,146], while others found no enhancement of aerobic power [134,144,147,148]. Similarly, some studies have shown an enhancement in performance following HIIT with nitrate compared to placebo [141,[144][145][146], while others found no benefit [134,148].…”
Section: Nitratementioning
confidence: 99%